Comparison of accommodations and interventions for youth with ADHD: A randomized controlled trial. (June 2020) - Harrison, Judith R.; Evans, Steven W.; Baran, Alyssa; Khondker, Fairooz; Press, Kathryn; Noel, Daphney; Wasserman, Shira; Belmonte, Colleen; Mohlmann, Morgan
Abstract: School psychologists have a variety of evidence-based interventions from which to choose when recommending classroom-based strategies for students with attention deficit hyperactivity disorder (ADHD); however, strategies frequently found on individualized education plans are accommodations designed to remove barriers to learning, which have limited empirical evidence. As such, the purpose of the current study was to compare the efficacy of three interventions (i.e., organization training, self-management, note-taking instruction) and three accommodations (i.e., organization support, extended time, copy of teacher notes) to address difficulties with organization and maintaining attention during a science lesson and associated independent practice. The study included 64 middle school students with ADHD randomized to either an intervention or an accommodation condition. The intervention group was further divided into two subgroups, consisting of (a) students who were willing to follow intervention procedures and (b) students who were not willing to follow the procedures (behavioral indicators of social validity). Results indicated that adolescents with ADHD in the intervention group were statistically significantly more likely to organize and maintain binder organization and to take complete and accurate notes than those in the accommodation group. In addition, exploratory analyses indicated that adolescents who demonstrated willingness to follow intervention procedures were more likely to be academically engaged during instruction and independent work and to complete independent work accurately than those who resisted the procedures.